Isolation and characterization of low-density polyethylene degrading and biosurfactant-producing bacteria from soils - George, Romi Marina (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.